Understanding, acknowledging and accepting the knowledge regarding the complication of post-placental intrauterine contraceptive device insertion - Agrawal, Rushabh H.; Shah, Krima V.; Patwa, Khusboo N.; Anand, Rakesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Intrauterine devices are an effective and increasingly popular from of reversible contraception and are most effective method of long-term contraception. Post placental intrauterine contraceptive devices insertion is done within 48 hours of birth which is ideal period ass women are strongly motivated to do so at this time. Aim was to understand knowledge, acceptance and complication of post placental intrauterine contractive device insertion. Methods: This was a prospective observational study conducted in obstetrics and gynecology department of a tertiary care centre from 1st September 2021 to 28th February 2022. Results: Total 84 patient were counselled out which 50 were willing for PPIUCD out of which 48 (58%) patients PPIUCD was inserted and 2 patients were deferred. Conclusions: PPIUCD was accepted in 50 (60%) of counselled total patients out which most of the patient were 20-29 years having graduate degrees and were mutipara most common cause of acceptance was that it is long term method of contraception most of the patient were counselled intrapartum and had vaginal method of delivery patient were minimum complications with most common complication of missing threads and expulsion.